Development and degeneration of the intervertebral discs. - Urban, J; Roberts, S (1995)
The intervertebral discs undergo profound changes in structure and composition during development and aging. They also degenerate much earlier than other cartilaginous tissues, and in severe cases may lose function completely. The reasons for this early degeneration are unknown, but external factors, such as mechanical overload on the spine, or smoking, may be involved. However, recent work has revived interest in the importance of genetic and developmental influences on the intervertebral discs.